PENGARUH SATISFACTION DAN INTERPERSONAL TRUST TERHADAP GUANXI VALUE (Studi pada Pedagang dan Pemasok Komputer di Kota Yogyakarta) - Jefri Heridiansyah (Universitas Islam Nahdlatul Ulama Jepara, 2012)
AbstractComputer dealers and suppliers relationship have been relying on trust. Computer dealers and suppliers are usually not aware of the relationship between on the run is guanxi. Parties concerned in this relitionship consumers and suppliers. This study aimed to determine the effect of interpersonal trust and satisfaction in the computer business guanxi value. The sample consisted of 30 respondents, supplier and computer trader in Yogya IT and Ramai Mall. Results of this study found that the